2021
DOI: 10.3389/fmars.2021.710200
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Endophytic Polyamine-Producing Streptomyces mutabilis UAE1 Isolated From Extreme Niches in the Arabian Gulf Promotes the Performance of Mangrove (Avicennia marina) Seedlings Under Greenhouse Conditions

Abstract: Mangrove forests in the Arabian Gulf are under continuous threat. To increase plantations of gray mangrove (Avicennia marina) in the United Arab Emirates (UAE), 27 endophytic actinobacterial isolates obtained from mangrove roots were in vitro pre-screened to detect the polyamines (PAs) [putrescine (Put), spermidine (Spd), and spermine (Spm)]. We also determined the abilities of the endophytic PA-producing actinobacterial isolates in enhancing the growth of A. marina under greenhouse conditions. Although three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…Streptomyces spp. may have one or multiple mechanisms to control fungal pathogens [10,14] and to promote growth in plants [21,22]. For instance, pathogen growth can be inhibited by the production of cell-wall-degrading enzymes (CWDEs), antifungal metabolites or siderophores [23,24], hyperparasitism [25] and competition for nutrients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces spp. may have one or multiple mechanisms to control fungal pathogens [10,14] and to promote growth in plants [21,22]. For instance, pathogen growth can be inhibited by the production of cell-wall-degrading enzymes (CWDEs), antifungal metabolites or siderophores [23,24], hyperparasitism [25] and competition for nutrients [26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, free-living soil bacteria isolated from the rhizosphere, also referred to as plant growth-promoting (PGP) bacteria (PGPB), have been shown to improve plant growth or increase yield especially in nutrient-impoverished environments (Bashan and de-Bashan, 2005;Hassan et al, 2019;Kumar et al, 2019). Seed or root inoculation with PGPB is a common agricultural practice currently in use to improve the productivity and yields of many plants, including halophytes (El-Tarabily et al, 2019, 2021Mathew et al, 2020;Moretti et al, 2020). PGPB may directly influence plant growth by enhancing the availability of essential nutrients such as phosphorous (P), nitrogen (N), and iron (Fe) (El-Tarabily and Youssef, 2010;Glick, 2015), stimulating transport in plants (Bertrand et al, 2000), and producing plant growth regulators (PGRs) such as auxins [e.g., indole-3-acetic acid (IAA)], cytokinins (CKs), gibberellins (GAs), and polyamines (PAs) (Bashan et al, 2004;Hassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In coastal wetlands, few studies have demonstrated the potential of using the PGPB isolated from mangrove roots and rhizosphere for arid mangrove reforestation (Bashan et al, 2009;El-Tarabily and Youssef, 2010;Castro et al, 2018;El-Tarabily et al, 2021). These reports have linked PGPB to the growth of mangroves through P-solubilization or N-fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of halotolerant plant growth-promoting endophytes (PGPEs) isolated from halophytes, e.g., Salicornia europaea , seems to be an appropriate solution in sustainable agriculture ( Davy et al, 2001 ; Furtado et al, 2019a , b ; Szymańska et al, 2019 ; Christakis et al, 2021 ; El-Tarabily et al, 2021 ). Endophytes (microorganisms living within plant tissues without causing any negative effect on host plants) associated with crops can directly (e.g., nitrogen fixation and phytohormone and siderophore synthesis) and/or indirectly (e.g., protection against pests and herbivores) stimulate plant growth and protect them against unfavorable environmental conditions ( Khan et al, 2016 ; Rabiey et al, 2019 ; Eid et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%